Race and ethnicity in context: international migration, political mobilization, and the welfare state. Issue 3 (19th February 2017) - Zamora-Kapoor, Anna; Moreno Fuentes, Francisco Javier; Schain, Martin
ABSTRACT: This manuscript reviews the literature on race and ethnicity in the political context. It discusses the most important scholarship on international migration, political mobilization, and the welfare state to date, to identify current gaps and emerging lines of inquiry. Future studies are needed to better understand the mobilization of immigrants by political parties, the role of local politics for a national electoral mobilization, and the relationship between local and national political areas for policy development.